Polygamy in the light of Maqāsid Al-Sharī‘a - Ghafoor, Zonera; Elatrash, Radwan Jamal Yousef (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, IIUM, 2021)
Islam provides a balanced way of life to humans with equal rights and justice. Intent of Sharia is to provide these rights to all followers irrespective of their gender, marital, social or economic status. From marital point of view, the widow and divorcedwoman has right of second marriage, either with a married man or unmarried. Similarly, a man has a right to have four wives at a time and this system is known as polygamy. This paper, in this context, explores the wisdom behind polygamy in the light of Maqāsīd Al-Sharī‘a.It tries to answer these questions: Is the law of polygamy allowed to fulfil one’s sexual desires legally? Secondly: what arethe implication of polygamy in the preservation of family/ human race and nipping the social evils like prostitution, suicidal intentions, and mental issues? This study is divided into three sections including:(1)A brief introduction to Maāsid-Al-Shariah; (2) Polygamy and its brief history; and (3) Wisdom behind polygamy in the light of Maqāsid Al-Sharī‘a